Instant Messaging and Relationship Satisfaction Across Different Ages and Cultures - Vauclair C-M; Rudnev M; Hofhuis J; Liu JH (Masaryk University, Faculty of Social Studies, 2023)
Research suggests that using IM is generally beneficial for maintaining personal relationships, yet well-being benefits are likely to be conditional on micro- and macro-level variables. This study investigates the link between IM use and relationship satisfaction across age groups using survey data collected from 19 countries (N = 20,358, age range 18-94, Mage = 41.0, SD = 14.6). The multilevel regression results revealed that (1) overall IM use with strong ties is positively related to individuals' satisfaction with their relationships across all countries and (2) this link is weaker among older people compared to younger ones. The hypothesized cross-level interactions were not statistically significant overall, yet comparing individual countries (e.g., Germany and Indonesia), which are on the opposite ends of the autonomy-embeddedness value dimension, suggests that the use of IM might indeed be more important for relationship satisfaction in more embeddedness-oriented cultures and relationship benefits may be more similar across age groups than in autonomy-oriented cultures. More large-scale cross-cultural studies and multilevel theories are needed to arrive at a more contextualized understanding of IM as a global communication phenomenon.
Keywords: relationship satisfaction; instant messaging; culture; wellbeing; age groups